Program Pengembangan Kewirausahaan Bagi Mahasiswa di Fakultas Ilmu Sosial Universitas Negeri Manado - Sisca B Kairupan; Jeane Tuilan; Jovita Wotulo; Jeane Mantiri; Hendry J. D. Tamboto; Antoimette L. G. Katuuk; Recky H. E. Sendouw (Denpasar Institute, 2021)
The aim of the Entrepreneurship Program at the Faculty of Social Sciences Unima is to create entrepreneurial students who are able to open jobs and leave the old paradigm that university graduates must become job seekers. Students of the Faculty of Social Sciences Unima have great potential to become successful entrepreneurs if they are given training and assistance in exploring business ideas, business planning, management in the aspects of production, administration and marketing. The problem is, so far the students have not found the above matters practically. Through this entrepreneurship development program students will be given training and mentoring as well as real experiences. The specific target to be achieved in this PPK is to produce 20 new entrepreneurs based on science and technology, and the experience in this coaching is translated into a scientific work that is presented at a national seminar and published in scientific journals in order to increase understanding of how this approach process is carried out in creating new entrepreneurs. As many as 5 entrepreneurs each year, we use the following methods: Entrepreneurship Training, Field Trips, Coaching, Monitoring, Financial Assistance, Technology Assistance and Problem Solving Assistance.